An Improved Procedure for the Synthesis of Aryl Phosphonates by Palladium-Catalysed Cross-Coupling of Aryl Halides and Diethyl Phosphite in Polyethylene Glycol. (June 2013) - Wang, Ping; Lu, Jie; Zhang, Zhan-Hui
A general and greener protocol for the synthesis of aryl phosphonates by the cross-coupling of aryl halides and diethyl phosphite using tetrakis(triphenylphosphine)palladiume/triethylamine/polyethylene glycol 600 [Pd(PPh3 )4 /Et3 N/PEG 600] as an efficient catalytic system has been developed. This procedure also avoids hazardous solvents and is therefore an eco-friendly alternative to the existing methods.